Heteromorph ammonites from the Upper Maastrichtian of Pondicherry, south India - Kennedy, W; Henderson, R (1992)
The heteromorph ammonites (Ancyloceratina) from the Upper Maastrichtian Valudavur Formation of Pondicherry, are revised in a sequel to the previously published account of the normally coiled Phylloceratina, Lytoceratina and Ammonitina. Twelve species referred to eight genera are recognized, of which Cyrtoptychoceras is a new representative of the Polyptychoceratinae. The fauna is of great importance in the development of heteromorph ammonite taxonomy, although a source of great confusion to previous workers. It represents the most diverse Upper Maastrichtian heteromorph assemblage known. -Authors